2002
DOI: 10.1046/j.1468-2982.2002.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Eye Pain: Indication for Triptans

Abstract: Management of pain is difficult in many eye diseases. Particularly in patients undergoing surgical procedures, postoperative intractable pain is a major concern and severely influences the patient's comfort. We present 13 patients (eight male, five female, mean age 36 years) in whom sumatriptan, a highly selective 5-HT1B/1D agonist that is normally used as a specific anti-migraine drug, was used for the treatment of pain following photorefractive keratectomy (PRK). In two patients both eyes were operated on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…157 Work from our laboratories was the first to show that anti-migraine drugs with agonist activity at 5-HT receptors might act at this synapse; 107 our later work demonstrated that this site of action was relatively specific for processing of sensory information from the dura mater and involved the 5-HT1D receptor subtype. 156 A similar mechanism may occur in the cornea because triptans have been reported to ease pain following keratotomy, 158 an effect that may also be mediated via 5-HT1D receptors. 159 Serotonin infusions themselves also suppress discharges of these first-order sensory neurons in cats.…”
Section: Cerebral Cortexmentioning
confidence: 96%
“…157 Work from our laboratories was the first to show that anti-migraine drugs with agonist activity at 5-HT receptors might act at this synapse; 107 our later work demonstrated that this site of action was relatively specific for processing of sensory information from the dura mater and involved the 5-HT1D receptor subtype. 156 A similar mechanism may occur in the cornea because triptans have been reported to ease pain following keratotomy, 158 an effect that may also be mediated via 5-HT1D receptors. 159 Serotonin infusions themselves also suppress discharges of these first-order sensory neurons in cats.…”
Section: Cerebral Cortexmentioning
confidence: 96%
“…115 Another attempt to control the pain level after surface ablation combines the use of triptanes, known from migraine therapy, with classic analgesic agents. 116,117 This strategy seems valuable as analgesic agents are known to have a poor effect on pain mediated by the trigeminal nerve. We have seen impressive results with rizatriptan 10 mg in some of our patients with disabling pain despite our routine prescription of oral acetaminophen (Paracetamol) and metamizole (Novaminsulfon).…”
Section: Complicationsmentioning
confidence: 99%
“…Migraine produces a pain in the dura and there are no reports of it producing pain centered on other “nociceptor‐only” trigeminal receptive fields such as the cornea or the teeth. The action of the triptans, for instance, is likewise confined to dural pain; there appears to be only one report of their use in eye pain 106 and apparently none at all of their successful use against toothache. The is one report on the action of sumatriptan as an analgesic in intestinal tract inflammation, 107 but the authors were unable to decide between a peripheral and a central action.…”
Section: A Pain In the Duramentioning
confidence: 99%